Nursing heroism in the 21st Century' - Darbyshire Philip (BMC, 2011)
Abstract Background The Vivian Bullwinkel Oration honours the life and work of an extraordinary nurse. Given her story and that of her World War II colleagues, the topic of nursing heroism in the 21st century could not be more germane. Discussion Is heroism a legitimate part of nursing, or are nurses simply 'just doing their job' even when facing extreme personal danger? In this paper I explore the place and relevance of heroism in contemporary nursing. I propose that nursing heroism deserves a broader appreciation and that within the term lie many hidden, 'unsung' or 'unrecorded' heroisms. I also challenge the critiques of heroism that would condemn it as part of a 'militarisation' of nursing. Finally, I argue that nursing needs to be more open in celebrating our heroes and the transformative power of nursing achievements. Summary The language of heroism may sound quaint by 21st Century standards but nursing heroism is alive and well in the best of our contemporary nursing ethos and practice.